Community Empowerment Through the Utilization of Microorganism Enzymes (EMO) to Enhance Food Security - Jumriah; Ferianzo, Nico; Sheftiana, Ulfah Sarach; Nico, Ratna Setiani; Dwinhoven, Ifhan; Relatami, Andi N Renita (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This community service program aimed to empower local communities by utilising Microorganism Enzymes (EMO) to support food security. EMO was applied to process organic waste into organic fertilizer as a substitute for chemical fertilizers, while also enabling the use of rainwater as a clean water source. The implementation methods included socialisation, training on EMO production, its application in agriculture, and an impact evaluation. The results indicated an increase in community knowledge and skills in producing and utilising EMO, as well as cost savings in fertilisers, pesticides, and water storage, along with improvements in the quality of urban vegetable production. This program contributes to achieving sustainable food security and aligns with the United Nations' Sustainable Development Goals (SDGs). Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation and Infrastructure